2011
DOI: 10.1172/jci42953
|View full text |Cite
|
Sign up to set email alerts
|

PML-RARA can increase hematopoietic self-renewal without causing a myeloproliferative disease in mice

Abstract: Acute promyelocytic leukemia (APL) is characterized by the t(15;17) translocation that generates the fusion protein promyelocytic leukemia-retinoic acid receptor α (PML-RARA) in nearly all cases. Multiple prior mouse models of APL constitutively express PML-RARA from a variety of non-Pml loci. Typically, all animals develop a myeloproliferative disease, followed by leukemia in a subset of animals after a long latent period. In contrast, human APL is not associated with an antecedent stage of myeloproliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…Our data extend previous studies linking PML/RARA to altered proliferation, [42][43][44] providing the novel finding that altered cell-cycle kinetics is a feature of PML/RARAexpressing cells at very early stages of the leukemogenic process. We found that the enhanced capacity for promyelocytes to proliferate depends on the PML part of the fusion and correlates with the ability to initiate leukemia, in line with previous findings.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data extend previous studies linking PML/RARA to altered proliferation, [42][43][44] providing the novel finding that altered cell-cycle kinetics is a feature of PML/RARAexpressing cells at very early stages of the leukemogenic process. We found that the enhanced capacity for promyelocytes to proliferate depends on the PML part of the fusion and correlates with the ability to initiate leukemia, in line with previous findings.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 89%
“…Finally, since we observed putative PML/RARA binding sites in our most down-regulated gene Ltf, we investigated binding of the fusion protein using chromatin immunoprecipitation. We confirmed binding and enrichment of PML/RARA at the Ltf locus (Online Supplementary Figure S7C), providing a mechanistic explanation for the strong deregulation observed.Our data extend previous studies linking PML/RARA to altered proliferation, [42][43][44] providing the novel finding that altered cell-cycle kinetics is a feature of PML/RARAexpressing cells at very early stages of the leukemogenic process. We found that the enhanced capacity for promyelocytes to proliferate depends on the PML part of the fusion and correlates with the ability to initiate leukemia, in line with previous findings.…”
supporting
confidence: 89%
“…In contrast, PR +/--derived BM cells have a competitive transplantation advantage, as demonstrated by an increased ability to contribute to peripheral blood lineages (especially myeloid) over time (39). To determine whether Dnmt3a is required for this competitive advantage, we mixed whole BM cells from mice with the indicated genotypes ( Figure 7A) at a ratio equal to that of WT competitor BM cells and transplanted the cells into lethally irradiated WT mice.…”
Section: Dnmt3a Is Required For a Pml-rara-driven Competitive Advantamentioning
confidence: 99%
“…19 In total, we identified 31 TF genes that were both targeted differentially by HoxB4 and exhibited differential expression between adjacent time points ( Figure 4A) 32,33 Stat5, 34 Tcf7, 35 and Pml-RARA. 36 Direct regulation of multiple hematopoiesis TFs by HoxB4 strongly implies that it is a master regulator positioned high in the hierarchy of the hematopoiesisregulatory network. Most of the TFs targeted by HoxB4 were either up-regulated or down-regulated; however, several TFs showed more complicated HoxB4 regulation ( Figure 4A).…”
Section: Dynamic Regulation Of Tfs By Hoxb4 During Esc Differentiatiomentioning
confidence: 99%